Opportunities for Carbon Dioxide Removal Within the United States Department of Agriculture - Jacobson, Rory; Sanchez, Daniel L. (Frontiers in Climate, 2019)
Farming and ranching communities in the United States sit at the front lines of climate change impacts and responses. In particular, terrestrial atmospheric carbon dioxide removal (CDR) can reduce climate change impacts while increasing resilience to extreme weather. Currently, many CDR technologies and strategies are still under research and development (R&D), and lack sufficient federal support to reach widespread deployment. Here, we provide an assessment of the United States Department of Agriculture’s (USDA) existing programs and organizational structure, its capacity to support research and demonstration of CDR, and recommendations for expansion of these capabilities. We summarize USDA’s previous and current efforts to incorporate CDR R&D within their research, education, and economics mission, as well as opportunities to refocus and expand existing programs. Potential future actions to expand CDR R&D capabilities include: 1) the establishment of a new extramural research agency and an intramural technology commercialization program within USDA, 2) improved coordination between the Foundation for Food and Agriculture (FFAR) and USDA, 3) improved intra-agency and inter-agency coordination, and 4) congressional action to establish and fund new CDR programs within USDA. USDA can pursue multiple strategies to enhance CDR, driving development, demonstration, and deployment across the United States.